Pembuatan Batako Menggunakan Plastik PET (Polyethylene Terephthalate) Sebagai Bahan Pengganti Pasir untuk Menentukan Nilai Kuat Tekan - Rikayasa, Rikayasa; Hermansyah, Hermansyah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
To preserve the environment, it is necessary to innovate the use of plastic waste in the manufacture of building materials. Innovations that can be applied to this brick mix are such as adding inorganic materials, one of which is by adding PET plastic as a substitute for sand to the brick mix to innovate and know the strength of the bricks. the authors added a mixture of PET plastics with plastic percentages of 0%, 20%, 25%, and 30%. The calculation of brick mix planning uses reference SNI-03-0349-1989 with a compressive strength plan of 10 MPa. Compressive strength tests have various compressive strength values, namely variations of 0%, 20%, 25% and 30% obtaining compressive strength values of 7.92 MPa, 7.24 MPa, 7.52 MPa, and 7.24 MPa. . The addition of plastic as a substitute for sand in too many bricks proved ineffective against bricks. This means that the use of too much plastic can cause mortar and plastic to not be able to lock each other.